2018
DOI: 10.1007/s00464-018-6199-8
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of assessment tools for laparoscopic suturing

Abstract: Through identification and evaluation of assessment tools, the results of this review could be used as a guideline when implementing assessment tools into training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…In a recent review, published after conducting our study, several assessment tools for laparoscopic suturing were identified and summarized according to the current validity evidence available and could, according to the authors, be used as a guideline when assessing tools into future training programs. 40 A limitation of this study is the short amount of trial time the participants were given to reach a reasonable handling time of both instruments. Another limitation of the study is that females were overrepresented (females 70% vs males 30%) in the group that began with the NNH.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, published after conducting our study, several assessment tools for laparoscopic suturing were identified and summarized according to the current validity evidence available and could, according to the authors, be used as a guideline when assessing tools into future training programs. 40 A limitation of this study is the short amount of trial time the participants were given to reach a reasonable handling time of both instruments. Another limitation of the study is that females were overrepresented (females 70% vs males 30%) in the group that began with the NNH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a pilot study that was presented at a Society of American Gastrointestinal and Endoscopic Surgeons (SAGES) conference showed the value of FFTs in providing feedback to improve trainee skill [ 29 ]. We have published a comprehensive literature review of available assessment tools for laparoscopic suturing skills in the OR, and procedures that commonly require laparoscopic suturing [ 30 ]. Based on the results, GOALS had the most validity evidence in the context of operative assessment through direct observation by an attending surgeon, which is why we have used GOALS for intraoperative assessment in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These changes include altering the angle of the camera "offset" with similar FLS tasks, backhanded suturing, restricted suturing within a confined working space, suturing under tension, as well as continuous suturing. 6,[13][14][15][16] There have been emerging studies for developing new models for advanced laparoscopic tasks which included continuous suturing with free needle and the Endo Stitch TM device. 6,7 There are still very limited low-cost validated solutions which utilize the widely available trainer box for laparoscopic intracorporeal continuous suturing.…”
Section: Discussionmentioning
confidence: 99%